Honorific Address and Linguistic Politeness in Uab Meto: A Sociolinguistic Study of the Numponi Speech Community - Florida Serli Molo; Viktorius P. Feka; Selfiana T. M. Ndapa Lawa (Insan Akademika Publications, 2026)
This study describes the forms and meanings of noble address terms and analyzes their functions within the politeness system of the Uab Meto (Manlea dialect) speech community in Numponi Village, Malaka Regency. A descriptive qualitative approach was employed, with data collected through participant observation and semi-structured interviews with three informants, one nobleman and two traditional elders. Data were transcribed, classified, and analyzed using sociolinguistic and politeness theorities. The findings identify two basic noble address terms: Pah (male) and Tua (female), which develop into four derivative forms, Pah Nasi, Tua Nasi, Pah Ana, and Tua Ana. These terms encode gender, age, and social status while simultaneously functioning as cultural symbols of respect, politeness, and communal identity. The use reflects Leech’s politeness principles, particularly the maxims of tact, approbation, and modesty, whcih are central to maintaining social harmony within the Numponi community. These findings suggest that noble address terms in Uab Meto are not merely linguistic conventions but serve as vital mechanisms for preserving cultural values and social order within the community. Therefore, documentation and conscious transmission of these address terms are essential for safeguarding the sociolinguistic heritage of the Uab Meto speech community in the face of cultural and linguistic change